The Role of Nutrient Intake During Pregnancy in the Development of Fetal and Infant Health - Nayla Alator (Journal of Nutrition and Health Care, 2024)
Pregnancy is a critical period in the human life cycle that requires special attention regarding nutritional intake to support foetal and infant development. This article investigates in depth the crucial role of nutritional intake during pregnancy in the development of foetal and infant health. First, we explore the influence of balanced nutrition on foetal growth by examining its positive impact on the formation of major organs and the development of the nervous system. Secondly, this article discusses the association between the intake of certain nutrients, such as vitamins, minerals and essential fatty acids, with birth weight adequacy and the risk of metabolic diseases at the infant stage. Furthermore, we detail the effects of nutrient deficiencies during pregnancy, highlighting the potential risks to premature birth, developmental abnormalities and other health problems in infants. In addition, the study considers the impact of excess intake of certain nutrients, providing insight into the potential risks associated with overconsumption that may affect foetal and infant health. Finally, the article presents the practical implications of the findings by highlighting the need for appropriate and customized nutritional guidance during pregnancy to improve the long-term health of children. In conclusion, an in-depth understanding of the role of nutrient intake during pregnancy may provide the basis for more effective prevention and intervention efforts to improve foetal and infant health.